2020
DOI: 10.21608/jssae.2020.79169
|View full text |Cite
|
Sign up to set email alerts
|

Soil Propertes, Nutrints availability and Wheat Productivity as affected By Compost and Nitrogen Sources

Abstract: Two field experiments were performed in Agricultural Farm of Sides Agricultural Research Station , ARC ,Beni-Suef Governorate , Egypt to investigate the effect of different levels of compost (0.0 , 4.8 and 9.5 Mg ha -1 ) and different nitrogen sources , i.e. , without ,ammonium ,sulphate (AS) , ammonium nitate (AN) and urea(U) on some soil chemical and physical properties after wheat harvested as well as wheat growth parameters ; yield and its components. The results show that all studied soil properties and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…Similar results were obtained by Saison et al (2006) who reported that compost improved soil fertility and increased soil organic carbon and nutrient availability. The beneficial effect of organic manures also reported by Mohamed et al (2020) who found that compost at rate of 9.5 Mg ha -1 improved soil fertility and subsequently wheat production.…”
Section: -Soil Propertiessupporting
confidence: 57%
See 1 more Smart Citation
“…Similar results were obtained by Saison et al (2006) who reported that compost improved soil fertility and increased soil organic carbon and nutrient availability. The beneficial effect of organic manures also reported by Mohamed et al (2020) who found that compost at rate of 9.5 Mg ha -1 improved soil fertility and subsequently wheat production.…”
Section: -Soil Propertiessupporting
confidence: 57%
“…Organic manures have the possibility of providing the energy of microflora, improving soil physical, chemical and biological properties, supplying nutrients. Compost soil addition was observed to possess positive impacts that aid crop growth, therefore, improving the crop phytonutritional components (El-Hadidi et al 2020 andMohamed et al 2020). Khaled et al (2011) reported that compost possesses a vital role in saltaffected soils because the organic material causes an improving the soil properties, which have been deteriorated to the extent that passage of both air and water becomes extremely difficult in these soils.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing application level in pots causes increasing the positive effect on soil properties, therefore, improvement of feverfew plants performance and their nutrients uptake. These results are in harmony with the obtained findings of Mohamed et al, (2020) who reported that compost caused the decline of soil pH value, thus increasing the availability of all nutrients except molybdenum element. Similar results were reported for improving plant chemical traits due to compost addition by Massoud et al, (2016) who found that chemical constituents on Yarrow plant leaves such as N P K nutrients (%), photosynthetic pigments i.e., chlorophyll a, b, total chlorophyll and carotenoids content (mg/g FW) and total carbohydrates (%) increased as the level of addition compost increased.…”
Section: Discussionsupporting
confidence: 92%
“…Organic manures possess the possibility of increasing soil aggregates, thus improving soil salt leach. Also it leads to provide the energy of microflora in addition to its ability to improve soil physical, chemical and biological properties and supply nutrients under salinity conditions (Al-Taey, 2017;Hafez et al, 2020;Emam et al, 2020 andMohamed et al, 2020). There are many researches with respect to the effect of organic amendments on plants grown on salt affected soil.…”
Section: Introductionmentioning
confidence: 99%